MENINGKATKAN SOLIDARITAS ANTAR TEMAN MELALUI BIMBINGAN KELOMPOK DI SD AL- MUTTAQIEN BOARDING SCHOOL SEMESTER GENAP TAHUN PEMBELAJARAN 2013/2014 - Arifin Nur Budiono (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
In order to be self-independet  learners  students  are highly required  to learn (Dimyati & Mudjiono, 2009: 5). According to Skiner (in Dimyati & MUdjiono, 2009: 9) learning is a behavior.  He  adds  that  when  students   are  learning  something,  they  will  get  better response.  On the other hand, their response  will decrease  when they are not learning. In accordance with the previous illustration, the researchers  conducted  abservation  in SD Al Muttaqien  Boarding School  Kaliwates. The result  of  the  observation  about  students’ solidarity suggest  tha  it is between  55% -64%. This study aimed  an investigating the  e increase  of students’  solidarity through  the  implementation  of the  group guidance. The researcher  employs classroom action research (CAR) as a research method. It includes two cycles. The results of this study on cycle I suggest 80 % and on cycle 2 85 %. Based on the result of questionaire, the highest score for the “yes” answer is 23 or 92%. Further, for the “No” answer the result is 8 or 32%. Based on the previous result, it can perfectly prove that the students’ solidarity can be signivicantly improved through the implementation  of this method. Keywords: Students’ solidarity, the group guidance